The Effect of Transformational Leadership, Work Engagement, and Quality of Work Life on Organizational Citizenship Behavior - Febriyanti, Carlintyas; Kurniawan, Ignatius Soni; Yulianto, Eko (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The phenomenon behind this study is that some employees of Next Hotel Yogyakarta still focus primarily on their main tasks and have not fully demonstrated extra-role behaviors, such as helping colleagues or taking initiatives beyond their formal responsibilities. This condition indicates that organizational citizenship behavior (OCB) has not yet been optimal within the work environment. This study aims to analyze the influence of transformational leadership, work engagement, and quality of work life on organizational citizenship behavior. The research employs a quantitative approach involving 50 employees of Next Hotel Yogyakarta, who were selected using a census sampling technique. Data were collected through a questionnaire distributed via a survey and based on indicators relevant to the variables studied. Data analysis was conducted using SmartPLS version 4.0 to test the relationships among variables. The results indicate that transformational leadership, work engagement, and quality of work life have positive and significant effects on organizational citizenship behavior. This study highlights the importance of improving OCB through the significant antecedents proposed.